Covalent organic frameworks from a monomer with reduced symmetry: polymorphism and Sierpiński triangles. Issue 90 (28th October 2019) - Cui, Daling; Fang, Yuan; MacLean, Oliver; Perepichka, Dmitrii F.; Rosei, Federico; Clair, Sylvain
Abstract : Polymorphism in surface-supported covalent organic frameworks grown from a low-symmetry precursor. Abstract : We report on the synthesis of a covalent organic framework based on the low-symmetry 1, 3-benzenediboronic acid precursor. Two distinct polymorphs are obtained, a honeycomb network and Sierpiński triangles, as elucidated by scanning tunneling microscopy. Control over polymorph formation was achieved by varying the precursor concentration for on-surface synthesis.